A review of the Tychus algericus species group (Coleoptera: Staphylinidae: Pselaphinae), North Africa - Sabella, Giorgio; Besuchet, Claude; Kurbatov, Sergey A. (Zootaxa, 2011)
The species belonging to the Tychus algericus group are revised and the group is characterized. Four species are recognized, described and illustrated, and a key for identification is provided. One species is new to science: T. similis Besuchet, sp. n. from Algeria, while three taxa: T. algericus Guillebeau, 1893 from Tunisia and Algeria, T. depexus Peyerimhoff, 1905 from Algeria, and T. vaucheri Jeannel, 1956 from Morocco are redescribed and their affinities and geographic distribution discussed. The lectotype for Tychus depexus is here designated.